DDX3X mRNA Expression in T Cells Is Associated with the Severity and Mortality of Septic Patients. (8th February 2022) - Liu, Yukun; Zhang, Yongsheng; Liu, Qinxin; Xie, Weiming; Wang, Xiang; Yang, Fan; Gao, Wei; Bai, Xiangjun; Li, Zhanfei; Wang, Yuchang
Abstract : Purpose. DDX3X acts as the critical checkpoint of death in stressed cells. The purpose of this study was to evaluate the mRNA expression level of DDX3X in T cells in peripheral blood of patients with sepsis and to explore its correlation with the prognosis of sepsis. Methods. Seventy-nine patients with traumatic sepsis were enrolled in this prospective cohort study. Blood samples were collected within 24 hours after the diagnosis of sepsis or septic shock, and the mRNA expression level of DDX3X in T cells was detected by PCR. Results. The level of DDX3X mRNA in T cells was significantly increased in septic patients as well as in septic shock patients. The level of DDX3X mRNA was negatively correlated with T cell count and positively correlated with acute physiological and chronic health assessment (APACHE) score and sequential organ failure assessment (SOFA) score (P < 0.01 ). The area under the curve (AUC) of the receiver operating characteristic (ROC) curve was 0.79 (95% confidence interval (CI), 0.68-0.90). A Cox proportional hazard model identified an association between an increased DDX3X mRNA level (≥1.575) and the risk of 28-day mortality (hazard   ratio = 9.540, 95% CI, 2.452-37.108). Conclusions. High level of DDX3X mRNA in T cells in sepsis is associated with the severity of sepsis and the mortality of patients with sepsis.